Comparison of antimicrobial dosing recommendations in patients receiving intermittent hemodialysis among drug information resources. (5th December 2021) - Lewis, Susan J.; Bodenhorn, Damon; Na, Eun‐Young; Jang, Soo Min
Abstract: What is known and objective: Tertiary drug information resources are frequently consulted for the optimal antimicrobial dosing in intermittent hemodialysis (IHD) patients. Yet, significant discrepancy may exist in dosing recommendations between resources. This study was to evaluate the consistency of antimicrobial dosing recommendations in IHD among four different drug information resources and the relevance of referenced pharmacokinetic studies. Methods: Dosing recommendations of 29 commonly prescribed antimicrobials in IHD patients were collected from Micromedex, LexiComp, Clinical Pharmacology and Drug Prescribing in Renal Impairment to compare dosing categorization and the total daily dose (TDD). Significant dosing discrepancies were defined as ≥30% difference. Referenced pharmacokinetic studies were evaluated for their relevance in current practice, using sample size, hemodialyzer types, the use of optimal pharmacodynamic targets and the consideration of different interdialytic dosing periods. Results and discussion: A significant variation was found both in dosing categorization and recommended doses between resources. Seventeen drugs were compared for TDD with significant dosing discrepancy in 8 drugs. Among 42 referenced pharmacokinetic studies, 40 were evaluated. Mean patient numbers of pharmacokinetic studies were 13 ranging from 3 to 70. Sixty per cent of studies utilized contemporary hemodialyzers (e.g., high‐flux and/or high efficiency). The optimal pharmacodynamic targets and the impact of different interdialytic intervals were assessed only in 27.5% and 7.5% respectively. What is new and conclusion: Inconsistent antimicrobial dosing recommendations for IHD patients exist among four well‐established resources. Many referenced pharmacokinetic studies utilized outdated or less pharmacodynamically relevant study methods. Newer studies are warranted to reflect contemporary dialysis practice and assess its impact on optimal antimicrobial dosing. Abstract : This study informs inconsistent antimicrobial dosing recommendations among four common drug information resources for patients receiving hemodialysis. Lack of clinical relevance was noted in many studies referenced in these resources to determine an optimal antimicrobial dosing for hemodialysis patients in contemporary practice.